If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-5) + -1(-8) + -4y + (-4x) + -1(-7y) + -1(-10x) = 0 -5 + -1(-8) + -4y + (-4x) + -1(-7y) + -1(-10x) = 0 Multiply -1 * -8 -5 + 8 + -4y + (-4x) + -1(-7y) + -1(-10x) = 0 Remove parenthesis around (-7y) -5 + 8 + -4y + (-4x) + -1 * -7y + -1(-10x) = 0 Multiply -1 * -7 -5 + 8 + -4y + (-4x) + 7y + -1(-10x) = 0 Remove parenthesis around (-10x) -5 + 8 + -4y + (-4x) + 7y + -1 * -10x = 0 Multiply -1 * -10 -5 + 8 + -4y + (-4x) + 7y + 10x = 0 Reorder the terms: -5 + 8 + (-4x) + 10x + -4y + 7y = 0 Combine like terms: -5 + 8 = 3 3 + (-4x) + 10x + -4y + 7y = 0 Combine like terms: (-4x) + 10x = 6x 3 + 6x + -4y + 7y = 0 Combine like terms: -4y + 7y = 3y 3 + 6x + 3y = 0 Solving 3 + 6x + 3y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + 6x + -3 + 3y = 0 + -3 Reorder the terms: 3 + -3 + 6x + 3y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 6x + 3y = 0 + -3 6x + 3y = 0 + -3 Combine like terms: 0 + -3 = -3 6x + 3y = -3 Add '-3y' to each side of the equation. 6x + 3y + -3y = -3 + -3y Combine like terms: 3y + -3y = 0 6x + 0 = -3 + -3y 6x = -3 + -3y Divide each side by '6'. x = -0.5 + -0.5y Simplifying x = -0.5 + -0.5y
| 77+5(x+9)=x | | 9x-(-7y)-(-6)+9-(-2x)-4y= | | (-x)-(-6)+(-4x)+(-7y)-1-8y= | | (-8)+(-8x)+(-y)+4+(-x)+(-9y)= | | -4a^3*2b^2= | | (-8y)-1+y+(-x)-3x-(-8)= | | 10x^24=56 | | 6x-293=6x-13 | | 3y+4+6x-3x-2y-2= | | 10y-6x+4-4x+6y-6= | | 5y-2y+5x+4x-7+9= | | b*c*d*c= | | 3y-1-2y-2x+8-4x= | | a*b*-3*-3= | | 64-6x=8-10x | | p*6*q*-1= | | -3*n*2*m= | | -2*4*m*m= | | y=x^2+(m-1)x+4 | | c*c*3*b= | | 4*a*b*4= | | m*2*n*3= | | c*c*c= | | b+4/4-b-10/2 | | b*b*a= | | 48x^2-8x^3=0 | | 7y^2-7y-15=0 | | 41-7x=2x+21 | | 6-9x=78-38x | | 4(c+3)=-4 | | 4(3+3)=-4 | | 10m=80 |